Chapter 16: Blockchain-enabled markets: A literature review - Wörner, Anselma; Tiefenbeck, Verena; Ketter, Wolfgang (Handbook of Information Systems and the Environment, 2023)
This comprehensive Research Handbook provides international perspectives on the role of information systems in environmental sustainability, drawing on ground-breaking research from leading scholars to predict future trends. Presenting in-depth studies which utilise a diverse range of research approaches and methods, this insightful Handbook provides a thorough examination of information systems research on environmental sustainability.<br
Keywords: Sustainable Information Systems; Green Information Systems; Energy Informatics; Pro-environmental Mindset and Behaviour; Digital transformation for sustainable markets and economies; Green Information Technology